Observation of Small-amplitude Electromagnetic Cyclotron Waves in the Solar Wind. (1st April 2023) - Yang, Hai-Feng; Zhao, Guo-Qing; Feng, Heng-Qiang; Pi, Gilbert; Liu, Qiang; Xiang, Liang; Li, Qiu-Huan; Ren, Dan-Yang
Abstract: Our previous studies on low-frequency electromagnetic cyclotron waves (ECWs) with amplitudes larger than 0.1 nT in the solar wind revealed that the left-handed (LH) polarized ECWs are the dominant waves, and these waves preferentially occur in plasma conditions of high proton speed ( V p ), high proton temperature ( T p ), low proton density ( N p ). In the present study, using magnetic field and plasma data from the Wind mission between 2005 and 2015, we perform a survey of small-amplitude ECWs with amplitudes smaller than 0.1 nT. It is revealed for the first time that the small-amplitude right-handed (RH) polarized ECWs tend to frequently occur in plasmas characterized by low V p, low T p, low N p, although the small-amplitude LH ECWs still preferentially occur in plasma conditions similar to the LH ECWs with amplitudes larger than 0.1 nT. Further investigation shows that the occurrences of small-amplitude RH ECWs and long-lasting radial interplanetary magnetic field (lrIMF) share the similar preferential plasma conditions of low T p and low N p . During lrIMF events, in particular, the occurrence rates of RH and LH ECWs are comparable, with the occurrence rate of small-amplitude RH ECWs slightly larger than that of small-amplitude LH ECWs. The generation mechanism of the small-amplitude ECWs is discussed.